2019
DOI: 10.1016/j.jclepro.2019.118069
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding eco-industrial parks through niche experimentation: Insights from three Italian cases

Abstract: Unfolding eco-industrial parks through niche experimentation: Insights from three Italian cases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…The keys to industrial symbiosis are collaboration and the synergistic possibilities offered by geographic proximity” (Chertow, 2007). Industrial symbiosis provides a competitive advantage that benefits enterprises in industrial parks because of the firms' agglomeration that utilize waste as a resource in production, making EIPs ideal sustainable industrial parks (Geng et al., 2009; Susur, Martin‐Carrillo, et al., 2019).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…The keys to industrial symbiosis are collaboration and the synergistic possibilities offered by geographic proximity” (Chertow, 2007). Industrial symbiosis provides a competitive advantage that benefits enterprises in industrial parks because of the firms' agglomeration that utilize waste as a resource in production, making EIPs ideal sustainable industrial parks (Geng et al., 2009; Susur, Martin‐Carrillo, et al., 2019).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…To understand the process and reasons for the transition of HIP to EIP, we used a framework based on the strategic niche management (SNM) framework proposed in the sustainability transition theory (Kemp et al, 1998) and subsequent perspectives on transitions to eco-industrial park development Susur, Martin-Carrillo, et al, 2019). We noted that modified the SNM perspective to conceptualize the unfolding of an EIP by evaluating them through the three niche processes: (1) articulation of expectations, (2) network building, and (3) learning, considering the EIPs as niches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As summarized by the United Nations Industrial Development Organization (UNIDO), an ecoindustrial park model is designed to consider the environmental dimension by encouraging the efficient use of resources, waste reduction and reuse, and chemical management (UNIDO, 2019). Many countries have adopted the industrial ecology concept (Piadeh et al, 2014;Industrial Estate Authority of Thailand, 2019;Susur et al, 2019;Hong and Gasparatos, 2020;Shah et al, 2020), and it was found to have successfully raised trust and improved relationship with adjacent communities (Yamsrual et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…One attractive way for achieving this is through creating industrial symbioses, phenomena inspired by natural ecosystems in which disparate organisms collaborate for mutual benefit. Recent successful examples for eco-industrial park (EIP) were demonstrated by the green transformation in China [4], unfold niche-building processes in Italy [5], and the superstructure optimization for a Mongstad, Norway case study [6].…”
Section: Introductionmentioning
confidence: 99%